The Influence of Dry Cupping toward Heart Rate Variability (HRV) in Male Obesity adolescence - Syahruramdhani, Syahruramdhani; Agustiningsih, Denny; Sofro, Zaenal Muttaqien (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2016)
Cardiovascular disease defines as a disease related to heart and blood vessel. One of high risk in the disease of cardiovascular is its on people with obesity. Heart Rate Variability (HRV) indicator is an important sign to identify cardiovascular risk and provide early information related to change of heart autonomy controlling. This indicator was influenced by several factors such as cupping therapy. Study found that HRV increased after cupping therapy by wet cupping treatment in healthy people. The aims of this research is to investigate the influence of dry cupping toward increased HRV in male obesity adolescence. The study was experimental with pre-post test design by using consecutive sampling of 30 male adolescence aged 18-24 years old with BMI ï³ 25 kg/m2. They were divided into 2 groups, control and intervention group with cupping therapy. Data result used in SDDN and RMSSD level. Analysis Data were used paired and independent t test. The result showed SDNN and RMMSD level before intervention were 73,95 ms dan 67,11 ms. Whereas SDNN and RMMSD level after intervention were 69,66 ms dan 61,95 ms. In paired (p=0,52 and p=0,38) and independent t test (p=0,30 and p=0,56) showed that there were no significant difference between SDNN and RMSSD in intervention group and control group (p>0,05). The conclusion of this study is dry cupping had no effects toward increased HRV level in male obesity adolescence.